2023
DOI: 10.1038/s41598-023-35641-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between microbiome diversity and epidemiology in domestic species of malaria-mediated mosquitoes of Korea

Abstract: Microbiota in the mosquito plays an important role in their behavior and vector competence. The composition of their microbiome is strongly influenced by the environment, especially their habitat. The microbiome profiles of adult female Anopheles sinensis mosquitoes from malaria hyperendemic and hypoendemic areas in Republic of Korea were compared using 16S rRNA Illumina sequencing. In different epidemiology groups, the alpha and beta diversity analyses were significant. The major bacterial phylum was Proteoba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The mosquito microbiome comprises a core microbiome essential for basic physiological functions and an environmental microbiome specific to particular habitats [ 35 ]. These characteristics of the mosquito microbiome were utilized to identify species biomarkers by considering the regional specificity and abundance of microorganisms [ 23 ]. These species biomarkers will be used as crucial biological clues for tracing mosquito movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mosquito microbiome comprises a core microbiome essential for basic physiological functions and an environmental microbiome specific to particular habitats [ 35 ]. These characteristics of the mosquito microbiome were utilized to identify species biomarkers by considering the regional specificity and abundance of microorganisms [ 23 ]. These species biomarkers will be used as crucial biological clues for tracing mosquito movement.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial community composition is influenced by the host’s genetic background, prolonged interactions with bacteria, and relationships between the microbiome and infectious pathogens. Previous studies have demonstrated distinct profiles in mosquito microbiomes in areas with and without a high prevalence of malaria [ 23 ]. Given the past detection of JEV in Cx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kruskal–Wallis H test was used to compare the results among developmental stages. To discover significant differences in their bacterial profiles, pairwise PERMANOVA was performed with the “beta-group-significance” tool in QIIME2 [ 44 ].…”
Section: Methodsmentioning
confidence: 99%